2023
DOI: 10.1177/13634607231193352
|View full text |Cite
|
Sign up to set email alerts
|

Queer kinship: Experiences of double-motherhood in Brazil

Abstract: A survey was conducted with nine Brazilian cisgender, non-heterosexual women who are mothers, with the aim of understanding the challenges faced by double-motherhood in Brazil. Nine interviews and one focus group were conducted online and asynchronously through WhatsApp. The data was transcribed and subjected to thematic analysis. The findings revealed four categories: IC as a form of resistance; violence and LGBTphobia against queer motherhood; the invisibility of queer motherhood in relation to the state; an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…To ensure the validity of their findings, Suter and colleagues [ 63 ] reported that the research team (a) maintained an analytic audit trail of data analysis and analytic decisions, (b) included data exemplars in the results section to demonstrate the link between raw data and analysis, and (c) used investigator triangulation and referential adequacy to verify the initial thematic analysis and interplay analysis. We were not able to find specific mentions of steps taken to enhance rigor in the studies by Hudak [ 66 ] and Ril and colleagues [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…To ensure the validity of their findings, Suter and colleagues [ 63 ] reported that the research team (a) maintained an analytic audit trail of data analysis and analytic decisions, (b) included data exemplars in the results section to demonstrate the link between raw data and analysis, and (c) used investigator triangulation and referential adequacy to verify the initial thematic analysis and interplay analysis. We were not able to find specific mentions of steps taken to enhance rigor in the studies by Hudak [ 66 ] and Ril and colleagues [ 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ril et al [ 67 ] sought to better understand the experience of double motherhood, which is the “shared experience of motherhood between two non-heterosexual cisgender women” (p. 2) by interviewing and conducting online focus groups with nine Brazilian cisgender lesbian or bisexual women who were mothers. One participant, Cloe, shared that she was not allowed to go with her daughter to the NICU because Cloe was a non-biological mother.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations